Effectiveness of Stretching Exercises on Musculoskateal Complaints in Workers - Amelia, Serly; Rukmana, Nova Mega; Putri, Dian Utama Pratiwi (Global Health Science Group, 2024)
Musculoskeletal complaints are conditions in which part of the muscular and skeletal system experiences pain problems. In 2022, 20 out of 35 workers at the UPTD Forest Management Unit in South Lampung experienced musculoskeletal complaints, resulting in absenteeism and decreased work productivity. Objective: The purpose of this study was to determine the effectiveness of stretching exercises for musculoskeletal complaints in workers at the UPTD Forest Management Unit in South Lampung in 2023. Method: The study used a Pre-Experimental design using the One Group Pretest – Posttest Design. The population was 35 workers, and the sample was 35 workers. The independent variable was stretching exercises, and the dependent variable was musculoskeletal complaints. Analysis used univariate and bivariate methods, with the Paired Sample T Test for bivariate analysis. Results: The results showed that the effect of stretching exercises on musculoskeletal complaints at the UPTD Forest Processing Unit in South Lampung was statistically significant, with a p-value of 0.000 <α = 0.05. Conclusions: The study concludes that stretching exercises are effective in reducing musculoskeletal complaints among workers at the UPTD Forest Management Unit in South Lampung. The results are expected to be applied to prevent health problems in workers, especially musculoskeletal diseases, and can be used as a consideration for continuing the program regarding the prevention of musculoskeletal complaints for office employees with a stretching exercise program that can be done in the workplace.